Experimentação de contramedidas para ataques em arquitetura BitTorrent - Bauermann, Daniel Rudi (Universidade do Vale do Rio do Sinos, 2009)
Currently Bit Torrent is one of the most popular technologies for file sharing in the Internet. Although its use is quite disseminated, several studieshave already showed that it is possible to explore the protocol's vulnerabilities to hamper content sharing. A recent study presented the first defense algorithms against such attacks on Bit Torrent networks. Albeit the results where satisfactory, the evaluation of those algorithms was made by simulation, with several simplifying assumptions. This dissertation presents the first results about the evaluation of countermeasure algorithms using real agents in a controlled environment. Besides the validation of simulation results, it was shown that it is possible to recover from attacks using this algorithms.
Keywords: BitTorrent; segurança; P2P; security; Ciências Exatas e da Terra